The Effects of Perceived Local Economic Conditions on Support for Sustainable Tourism Development at a World Heritage Site Destination (Journal of Governance and Development (JGD), 2019)
In general, tourism is often perceived as a catalyst for economic development at tourist destinations, especially in the developing countries. However, very little studies have systematically examined this relationship. Therefore, this study attempts to conï¬rm the relationship between perceived local economic condition and residentsâ€™ support for sustainable tourism development. For that purpose, a structured questionnaire was administered to gather responses from local residents who live in Lenggong district, one of Malaysiaâ€™s World Heritage Site destinations. The data was then treated with statistical analysis including descriptive analysis and simple regression. The outcomes of the study indicated that, perceived local economic condition was found to establish an inverse relationship with support for sustainable tourism development. In other words, when the local residents perceived the local economic as poor, they became very supportive of tourism development as an alternative to boost the local economy.